Development of a method to assess compliance with ergonomic posture in dental students - Nordi Sasso Garcia, Patricia Petromilli [UNESP] (2018)
Context: The ergonomic posture protocol is extremely important for the maintenance of occupational health in dentistry. The lack of compliance with this protocol results in a high risk of developing musculoskeletal disorders. Aims: This study developed a direct observation method for the evaluation of dental student compliance with ergonomic posture protocol. Subjects and Methods: The method is named compliance assessment of dental ergonomic posture requirements (CADEP). During the development of the method, 14 items were elaborated considering the theory of dental ergonomics. Each item should be classified as appropriate, partially appropriate, or inappropriate. After evaluation, all item values should be added, and the final score expressed as the percent of compliance with correct postures, with a score range of 0%-100%. Statistical Analysis Used: The reliability of CADEP was assessed through intra- and interobserver reproducibility. For the CADEP application, 73 senior year students from the undergraduate course in dentistry were evaluated. The intra- and interexaminer concordance was estimated using the intraclass correlation coefficient (rho). A descriptive statistical analysis was performed. Results: The reproducibility of evaluator 1 (rho =0.90; confidence interval [CI] 95%: 0.83-0.94), evaluator 2 (rho = 0.83; CI 95%: 0.70-0.90), the interexaminer in the first evaluation (rho = 0.81; CI 95%:0.67-0.89), and in the second one (rho = 0.76; CI 95%: 0.59-0.87) was classified as good. In the analysis of the compliance, it was verified that moderate compliance was the most prevalent among the evaluated students (65.6%, CI 95%: 60.3%-70.7%). Conclusions: CADEP was valid and reliable for the assessment of dentistry students' compliance regarding ergonomic posture requirements.